The Routledge companion to Jewish philosophy
1 online resource.
Keywords: "The Routledge Companion to Jewish Philosophy is a deep and broad reference that brings diverse perspectives to bear on the key topics, problems, and debates in Jewish philosophy and philosophical theology. The 37 chapters were written by an international team of experts from different traditions in philosophy and beyond and appear in print for the first time in this Companion. The chapters are divided into ten major sections: I. God II. Humanity III. From God to Us IV. From Us to God V. Jewish Mysticism VI. Faith and Reason VII. Judaism and Normativity VIII. Judaism and Politics IX. Judaism and Other Faiths X. Times and Trends A list of Related Topics at the end of each chapter and a comprehensive index at the back of the volume help readers navigate the Companion, and Further Reading sections at the end of each chapter identify the best avenues for future research. The volume is essential reading for students and scholars interested in Jewish philosophy, theology, religious studies and related subjects"--